Aligning indicators of community composition and biogeochemical function in stream monitoring and ecological assessments. (January 2016) - Parr, Thomas B.; Cronan, Christopher S.; Danielson, Thomas J.; Tsomides, Leonidas; Simon, Kevin S.
Abstract: Reliable and inexpensive indicators of ecosystem function are essential for accurately monitoring and describing ecosystem integrity. Currently, most state and federal assessments of aquatic ecological integrity rely on structural indicators and assume tight coupling of structure and function. We used fluorescent composition of dissolved organic matter as a metric for certain ecosystem functions and compared the resulting index of autochthonous microbial dissolved organic matter (DOM) to macroinvertebrate indicators and classifications of water quality attainment reported by the Maine Department of Environmental Protection (Maine DEP) at 142 stream sites. We observed that metrics of sensitive insect orders such as relative Plecoptera generic richness, relative Ephemeroptera abundance, and generic richness of EPT (Ephemeroptera, Plecoptera, and Trichoptera) were negatively correlated with higher values of metrics based on autochthonous microbial DOM sources. At the same time we observed an increase in the Hilsenhoff Biotic Index with increasing microbial DOM. We compared the abundance of this microbial DOM component to Maine DEP measured attainment classes and found that microbial DOM generally separated sites with high biological integrity from sites where the biotic community was highly degraded. This highlights that measures of biogeochemical ecosystem function complement measures of structure in biological assessments.